"Senobi" Stretch Ameliorates Asthma Symptoms by Restoring Autonomic Nervous System Balance. (1st December 2010) - Sato, Kazunari; Kawamura, Toshihiko; Abo, Toru
Abstract : The number of asthmatic patients is increasing in Japan. It is conceivable that changes in lifestyle (eg, lack of exercise and high-energy diet) may be associated with this phenomenon. The resulting factor seems to be altered activity of autonomic nervous system of these patients. When this activity was estimated by the measurement of heart rate variability, asthmatic patients (n = 11) showed a tendency for parasympathetic nerve dominance in comparison with healthy controls (n = 10). We recommend the patients engage in the "Senobi" stretch exercise, which involves stretching the arms and body upward while standing. After 1 month of regularly performing this exercise, most patients showed a decrease in the frequency of asthma rescue medication use. They also showed a recovery of forced expiratory volume in 1 second. These results suggest that the Senobi stretch is a useful exercise for asthmatic patients to perform to achieve a desirable improvement in symptoms.